PENGARUH VARIASI TEMPERATUR HIDROCRACKING TERHADAP INDEKS BIAS PRODUK HIDROCRACKING MINYAK JARAK PAGAR DENGAN KATALIS Mo-ZAA - Yulian Syahputri; Ady Mara (Universitas Pakuan, 2016)
This research aim to determine the influence of hydrocracking temperature variation to refraction index of hydrocracking castor oil product by using Mo-active natural zeolite catalyst. Hydrocracking process of castor oil was conducted with variation of temperature 250oC, 300oC, 350oC, 400oC, 450oC, 500oC and 550oC, whereas the flow rate of hydrogen gases 3.5 mL/min and the weight of catalyst 1.5 g. The refraction index of hydrocracking product of castor oil was analysed by using refractometer instrument. The result of this research showed that the best value of refraction index was 1.4681 which operated at 300oC temperature of hydrocracking.Key words : hydrocracking, catalyst, castor oil, refraction index